Patent Blue dye allergy and the deep inferior epigastric perforator free flap: a unique interaction. Issue 4 (8th February 2018) - Kumar, Shanesh; Dhillon, Raminder; Shah, Snehal; White, Dean C.; Rozen, Warren Matthew
Key Clinical Message: Patent Blue dye for sentinel lymph node biopsy is associated with systemic allergic response and generalized blue hue. We report a unique case of successful free flap transfer in this setting. Despite inotropic support and abnormal blue hue, allergic response does not preclude safe flap transfer and monitoring. Abstract : Patent Blue dye for sentinel lymph node biopsy is associated with systemic allergic response and generalized blue hue. We report a unique case of successful free flap transfer in this setting. Despite inotropic support and abnormal blue hue, allergic response does not preclude safe flap transfer and monitoring.